Islamic Sciences in Transition: Post-Reformation Developments in Indonesia’s State Islamic Universities - Muthohirin, Nafik; Aziz, Ahmad Amir; Mahfud, Choirul; Mukhlis, Fahrudin; Hikmawati, Rosyidatul (Universitas Islam Negeri Mataram, 2025)
The transition of State Islamic Colleges (IAIN/STAIN) to State Islamic Universities (UIN) marks a fundamental shift in the institutional structure and epistemology of Islamic higher education in Indonesia. This article critically investigates the new form of UIN following the transformation era, which successfully integrated Islamic sciences with modern disciplines. Institutional transformation and the development of Islamic thought through an integrative, academic, and contextual paradigm have contributed to this successful transition. This reflects how UIN transformation has become more accommodative and inclusive, with deliberate efforts to integrate various fields of religious and modern sciences. This research is based on a qualitative study using document analysis, expert interviews, and focus group discussions. The article also traces the early dynamics of academic Islamic studies, the emergence of the conversion project, and examines its evolution in the current post-reform era. It argues that significant institutional dynamics and epistemological shifts have revived the academic and critical paradigm of Islamic sciences. Thus, UIN has emerged as a center for multidisciplinary Islamic intellectual currents that are responsive to humanitarian issues and global Islamic academic discourse.